Biosensing with Virus Electrode Hybrids. Issue 2 (1st June 2015) - Mohan, Kritika; Penner, Reginald M.; Weiss, Gregory A.
Abstract : Virus electrodes address two major challenges associated with biosensing. First, the surface of the viruses can be readily tailored for specific, high affinity binding to targeted biomarkers. Second, the viruses are entrapped in a conducting polymer for electrical resistance‐based, quantitative measurement of biomarker concentration. To further enhance device sensitivity, two different ligands can be attached to the virus surface, and increase the apparent affinity for the biomarker. In the example presented here, the two ligands bind to the analyte in a bidentate binding mode with a chelate‐based avidity effect, and result in a 100 pM experimentally observed limit of detection for the cancer biomarker prostate‐specific membrane antigen. The approach does not require enzymatic amplification, and allows reagent‐free, real‐time measurements. This article presents general protocols for the development of such biosensors with modified viruses for the enhanced detection of arbitrary target proteins. © 2015 by John Wiley & Sons, Inc.